ANALISIS NIAT PEMBELIAN KONSUMEN PADA KONTEN AFFILIATE TIKTOK SHOP DENGAN PENDEKATAN SYSTEMATIC LITERATURE REVIEW - Devita Fahliza Ulfa; Arista Pratama; Siti Mukaromah (CV. Adiba Aisha Amira, 2026)
This study aims to analyze factors influencing purchase intention in affiliate content on TikTok Shop using a Systematic Literature Review (SLR) approach. The review examines 30 empirical articles published between 2022 and 2026, sourced from scientific databases such as Google Scholar, Scopus, ScienceDirect, and Emerald Insight. The SLR process was conducted systematically through planning, execution, and reporting stages, with research questions formulated using the PICOC framework. The findings indicate that trust, habit, perceived value, hedonic motivation, and performance expectancy are the most influential factors affecting purchase intention in the context of social commerce. Among these, trust and habit emerge as the most dominant variables. The study also reveals that the UTAUT2 model is the most widely used theoretical framework, often extended with additional variables to better explain consumer behavior in digital environments. In terms of methodology, most studies employ a quantitative approach using Structural Equation Modeling (SEM). Furthermore, the results show a growing trend of research in social commerce over recent years. However, studies specifically focusing on affiliate content on TikTok Shop remain limited, indicating opportunities for future research. This study provides a systematic overview of existing literature and contributes to a better understanding of purchase intention in social commerce.